2013
DOI: 10.1016/j.juro.2012.10.061
|View full text |Cite
|
Sign up to set email alerts
|

25-Year Disease-Free Survival Rate After Irradiation for Prostate Cancer Calculated with the Prostate Specific Antigen Definition of Recurrence Used for Radical Prostatectomy

Abstract: With this irradiation program cancer control, defined using the recurrence definition for radical prostatectomy, was durable with no further recurrence between 15.5 and 25 years of followup. This study also suggests that at least 15 years of followup are necessary to fully evaluate any prostate cancer treatment. Furthermore, if prostate specific antigen is less than 0.20 ng/ml 15 years after treatment, later recurrence should be unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 14 publications
2
25
0
3
Order By: Relevance
“…12 Critz et al used a definition of <0.2 ng/ mL for BCR to compare their results post-PB with patients treated by RP and analyzed for low-, intermediate-and highrisk cancers over the same time range. 11 Using the same definition (<0.2 ng/ml) for both treatment modalities (PB vs. RP) gave similar results for 10-and 15-year DFS. Selecting patients who are treated during the same time span allows for comparison of Gleason scores and PSA levels that prescribe a therapy for active surveillance or initiate active treatment.…”
mentioning
confidence: 70%
“…12 Critz et al used a definition of <0.2 ng/ mL for BCR to compare their results post-PB with patients treated by RP and analyzed for low-, intermediate-and highrisk cancers over the same time range. 11 Using the same definition (<0.2 ng/ml) for both treatment modalities (PB vs. RP) gave similar results for 10-and 15-year DFS. Selecting patients who are treated during the same time span allows for comparison of Gleason scores and PSA levels that prescribe a therapy for active surveillance or initiate active treatment.…”
mentioning
confidence: 70%
“…This early report is a retrospective multicentre cohort study and gives an efficient picture of the practice of BT in Italy, including 20 but there may be an increased toxicity, 21 and LDR-BT alone can produce excellent biochemical control for low-as well as intermediate-risk disease. 4 Approximately 40% of patients in the present series had previously undergone neoadjuvant AD therapy for 3-6 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, using different definitions to compare the oncologic outcome of radiation therapy to that of radical prostatectomy is questionable. To address this issue, Critz et al reported the oncologic outcome in patients who received LDR-brachytherapy in combination with EBRT using the same definition for biochemical recurrence as that for surgery [15]. They concluded that the biochemical recurrence-free rate was similar to that of radical prostatectomy using a large cohort study.…”
Section: Discussionmentioning
confidence: 99%